LEGAL AND POLITICAL ASPECTS OF SOVIET-GERMAN URANIUM MINING IN THE SOVIET OCCUPATION ZONE OF GERMANY (SBZ) AND THE GDR - Brumme, Reiner (E-Journal VFU, 2025)
The Soviet nuclear weapons programme, which was stepped up from 1945, required a lot of uranium. The Soviet Union itself only had a few small deposits in the Central Asian Soviet republics. It was dependent on uranium from countries in its sphere of influence. This included the Soviet Occupied Zone, from which the Soviet Union was to receive its reparations for war damage caused by Germany in accordance with the Potsdam resolutions of the three Allies. The Soviet Occupation Zone had suspected uranium deposits in the Saxon Ore Mountains, which, together with neighbouring deposits discovered in Thuringia, developed into the largest deposits in the entire socialist camp with the delivery of around 216,000 tonnes of enriched uranium. The article deals with the legal and political aspects of this uranium mining, which was initially purely Soviet from 1945 to 1953 and Soviet-German from 1954 onwards.
Keywords: atomic bomb; SAG Wismut; SDAG Wismut; Soviet-German uranium mining; Soviet occupation zone of Germany; uranium